2022
DOI: 10.3390/ijms23105393
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Mitochondrial D-Loop Region Methylation Levels in Mild Cognitive Impairment Individuals

Abstract: Methylation levels of the mitochondrial displacement loop (D-loop) region have been reported to be altered in the brain and blood of Alzheimer’s disease (AD) patients. Moreover, a dynamic D-loop methylation pattern was observed in the brain of transgenic AD mice along with disease progression. However, investigations on the blood cells of AD patients in the prodromal phases of the disease have not been performed so far. The aim of this study was to analyze D-loop methylation levels by means of the MS-HRM techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…( Bellizzi et al, 2013 ; Dostal and Churchill, 2019 ). MtDNA methylation and hydroxymethylation have been shown that these changes have effects on neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis ( Blanch et al, 2016 ; Stoccoro et al, 2018 ; Nikolac Perkovic et al, 2021 ; Stoccoro and Coppedè, 2021 ; Stoccoro et al, 2022 ). Several animal studies have shown TET-mediated antidepressant-like effects, but most of them are related to nuclear epigenetic regulation.…”
Section: Mtdna Methylation/hydroxymethylationmentioning
confidence: 99%
“…( Bellizzi et al, 2013 ; Dostal and Churchill, 2019 ). MtDNA methylation and hydroxymethylation have been shown that these changes have effects on neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis ( Blanch et al, 2016 ; Stoccoro et al, 2018 ; Nikolac Perkovic et al, 2021 ; Stoccoro and Coppedè, 2021 ; Stoccoro et al, 2022 ). Several animal studies have shown TET-mediated antidepressant-like effects, but most of them are related to nuclear epigenetic regulation.…”
Section: Mtdna Methylation/hydroxymethylationmentioning
confidence: 99%
“…The D-loop region of the mitochondrial genome regulates the replication of mtDNA and its transcription [ 141 , 142 , 143 , 144 ] and is methylated in both model animals and humans [ 145 , 146 ]. Both the hypo- and hypermethylation of the D loop have been observed in AD [ 138 , 140 , 147 ]. This variation in the degree of methylation might be explained by variations in disease stage or the brain area used for the analysis.…”
Section: Role Of 1c Metabolism In Epigenetic and Post-translational M...mentioning
confidence: 99%
“…The BIN1 gene, encoding for the bridging integrator 1, is the second most important susceptibility gene for late-onset AD after the APOE gene, and interestingly, two large independent autopsy studies showed that there were methylation changes in the BIN1 of the AD patient’s brain, accompanied by high expression of BIN1 [ 41 , 70 ]. We recently identified mtDNA higher D-loop methylation levels, which regulates both mtDNA replication and gene expression, in MCI patients characterized by neurological examination, CSF biomarkers, and neuroimaging analyses compared to control subjects and AD patients at both early and advanced stages of the disease [ 71 ]. Moreover, higher D-loop methylation levels were detected in controls compared to AD patients in advanced stages of the disease, but not in those at early stages.…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%
“…Similarly, in recent years we have seen increasing evidence that epigenetic modifications of mitochondrial DNA (mitoepigenetics) also likely play a significant role in the etiology of several human diseases, including cancer, obesity, diabetes and cardiovascular and neurodegenerative diseases [ 113 ]. However, until now only one study investigated mitoepigenetic modifications in the peripheral blood of patients with MCI [ 71 ], and results suggest that this field of research deserves to be further investigated. Another issue that should be addressed in future studies is the investigation of environmental factors to which individuals have been exposed during their life, since they can play an important role in the etiology of AD [ 114 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%